Graduate employability and internationalization in vocational higher education: An integrated institutional framework from a five-year case study - Endang Soelistiyowati; Yohana Ika Harnita Sari; Shinta Dewi Novitasari (Jurnal Pendidikan Vokasi, 2026)
Graduate outcome evaluation in Indonesian vocational higher education often emphasizes employment status and waiting time while giving limited attention to how institutional strategies shape employability and internationalization. This study examines how tracer studies, alumni feedback, student mobility, and institutional partnerships reflect strategic efforts at Sekolah Vokasi Universitas Gadjah Mada from 2021 to 2025. Previous research has typically examined tracer studies, partnerships, alumni feedback, and student mobility as separate areas of inquiry. In contrast, this study integrates these institutional evidence sources into a unified employability–internationalization framework. This framework demonstrates that graduate readiness emerges from interconnected institutional mechanisms linking curriculum development, workplace learning, institutional partnerships, alumni feedback, and international exposure. The findings reveal consistently high tracer study participation and a generally positive school-to-work transition, with most graduates securing employment before graduation or within six months after graduation. Student mobility records indicate stronger institutional capacity for internationalization at home than for outbound mobility. Partnership records demonstrate substantial institutional collaboration capacity; however, their contribution depends on effective implementation through internships, curriculum development, professional certification, mobility programs, mentoring, and graduate recruitment activities. This study contributes an integrated employability–internationalization framework that conceptualizes tracer studies, alumni feedback, partnership activation, and student mobility as complementary institutional mechanisms for enhancing curriculum quality, workplace learning, international engagement, and graduate development. As a single-institution case study, the findings are context-specific and do not permit examination of individual-level relationships between participation in mobility or partnership activities and graduate career outcomes.